The association between the sense of control and depression during the COVID-19 pandemic: a systematic review and meta-analysis - Msetfi, Rachel M.; Kornbrot, Diana E.; Halbrook, Yemaya J. (Frontiers in Psychiatry, 2024)
Introduction. High levels of depression and low sense of control were reported during the Covid-19 pandemic. The removal of typical freedoms through public health restrictions may have played a role in this. The aim of this review was to review data collected during the pandemic and (1) estimate the strength of the association between sense of control and depression, (2) examine whether the different types of control measured affected the strength of the association and (3) whether this changed as a function of pandemic indicators.Methods. We conducted a systematic review and meta-analysis of studies, published in English, conducted between December 2019 and November 2022. 993 articles were identified, of which 20 were included in the review and 16 included in the meta-analysis after conducting a quality assessment using the standard NIH tool. Results. The controldepression association gave a bias independent pooled effect size of r = .41, and grew stronger over the 130 weeks covered by this review, but did not change as a function of local covid incidence rates. Subgroup analyses showed the external and overall control were more strongly related to depression than internal control. Discussion. These findings emphasise that factors external to the person are important to the sense of control and the importance to mental health of preserving the sense of control in situations where removal of personal freedoms is necessary such as public health emergencies.